1985
DOI: 10.1080/00288233.1985.10420928
|View full text |Cite
|
Sign up to set email alerts
|

Seedling appearance, survival, and development of ‘Grasslands Huia’, ‘Grasslands Tahora’, and Kent wild white clover cultivars after surface sowings in summer-moist hill country

Abstract: Seedling appearance, survival, and development of 'Grasslands Tahora', 'Grasslands Huia', and Kent wild white clover (Tr~rolium repens L.) cultivars were measured in various sward treatments after 4 surface sowings on summer-moist hill country. Huia seedling appearance was greatest in all treatments except the spring 1983 sowing when Huia and Tahora were equal. Tahora seedling appearance was superior to Kent in autumn and spring 1983, and similar in autumn and spring 1982. Seedling appearance differences were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Seedling appearance was more rapid and complete than that of KENT and TAHORA. Survival of seedlings was equal to TAHORA and superior to KENT (Chapman & Fletcher 1985). High persistence in Mackenzie high country, New Zealand (Scott 1985).…”
Section: Agronomic Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Seedling appearance was more rapid and complete than that of KENT and TAHORA. Survival of seedlings was equal to TAHORA and superior to KENT (Chapman & Fletcher 1985). High persistence in Mackenzie high country, New Zealand (Scott 1985).…”
Section: Agronomic Performancementioning
confidence: 99%
“…High autumn clover content compared to other New Zealand cultivars (Caradus 1991) Had third highest clover DM yield behind CRAU and DEMAND among 110 cultivars evaluated under rotational grazing in New Zealand (Woodfield & Caradus 1994 Description: Medium-leaved; shoot morphology and growth habit is dense, more erect than KENT or TAHORA; roots have some taproot production ). Lower stolon branching density than KENT, TAHORA, PRESTIGE, and DEMAND but greater stolon density than PITAU (Chapman & Fletcher 1985, DSIR Grasslands 1992. Moderate-high cyanogenesis levels (Mika 1984;Wheeler & Vickery 1989;Lehmann et al 1990;Crush & Caradus 1995) with 80% of plants cyanogenic (Caradus et al 1989a).…”
Section: Origin and Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies comparing paraquat andglyphosate (e.g., 0.8 kg a.i./ha and 2.16 kg a.i./ha respectively Chapman & Fletcher 1985), 0.25 kg a.i./ha and 2.0 kg a.i./ha respectively (Sithamparanathan et al 1986» have found similar and satisfactory establishment of grasses and legumes. However, Sithamparanathan et al (1986) stated "that these experimental rates resulted in almost complete kill of all resident grasses" and therefore scope for differential performance of herbicides was negligible.…”
Section: Introductionmentioning
confidence: 99%
“…'Grasslands Wana' cocksfoot (Dactylis glomerata L.) (Barker et al 1985), 'Grasslands Maru' phalaris (Phalaris aquatica L.) (Rumball 1980), and 'Grasslands Tahora' white clover (Trifolium repens L.) (Chapman & Fletcher 1985) are cultivars with potential for use in hill country and/or dry environments. On steep uncultivable hill country, surface oversowing is the only means of introducing improved pasture species into existing swards.…”
Section: Introductionmentioning
confidence: 99%